Improving quality in outpatient services - Guinane, Carole S. (Productivity Press, 2011)
A valuable reference for those involved in the field of ambulatory patient care, Improving Quality in Outpatient Services offers time-tested instruction on how to create a world-class outpatient program. It supplies a high-level overview of current opportunities, national quality programs, and challenges?outlining the policies, procedures, and plans required for success.